Institutional Ownership, CFO Competency and Environmental Uncertainty as moderating on Tax Avoidance Evidence: Indonesia - Simamora, Lolita Riantida; Sari, Dahlia (Prosiding International Conference on Sustainable Innovation (ICoSI), 2023)
This study aims to determine the effect of institutional ownership and the competence of the Chief Financial Officer (CFO) on tax avoidance with environmental uncertainty as a moderating variable. Institutional ownership is more motivated and able to intervene on tax avoidance. The population of this study are companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period and using a purposive sampling method. This study uses balanced data panel. Population using all companies is listed on IDX. The number of observations of sample data is 474 company years from 2016-2021. This study also involved statistical testing based on panel data regression. Measurement of tax avoidance using Current Effective Tax Rate. The results show that institutional ownership and CFO competency is positively related to tax avoidance and environmental uncertainty can weaken the negative relationship of institutional ownership to tax avoidance but can strengthen the positive relationship of CFO to tax avoidance. Based on this study, the regulator is considering more on tax regulation and penalties to reduce tax avoidance behavior.